The Effect of Experience and Professionalism on Auditor Performance in Accounting Firms in Jakarta and Surabaya During the Covid-19 Pandemic - Nurhadi, Hadi; Nur, Basyiruddin; Abbas, Yeni Elfiza; Andru, Budi (Journal of Accounting, Business and Finance Research, 2022)
The purpose of this study is to determine the effects of experience and professionalism on an auditor’s performance. The population of this research comprises nine public accounting firms and 170 auditors as respondents from public accounting firms throughout Jakarta and Surabaya, Indonesia. The method in this research is quantitative with a primary data type. The sampling technique is an analysis of the outer model (measurement model) and inner model (structural model) using the multivariate structural equation model (SEM) in SmartPLS 3. The results of this study indicate that the experience of auditors influences their performance rather than their professionalism. Simultaneously, the R-squared (R2) value is 0.96, or 96%, which means that an auditor’s performance is influenced by their experience and professionalism.